Neutrophil L-Plastin Controls Ocular Paucibacteriality and Susceptibility to Keratitis - Lu, Xiaoxiao; Kugadas, Abirami; Smith-Page, Kirsten; Lamb, Jeffrey; Lin, Tiffany; Ru, Yusha; Morley, Sharon Celeste; Fichorova, Raina; Mittal, Sharad K.; Chauhan, Sunil K.; Littleton, Sejiro; Saban, Daniel; et al. (Frontiers in Immunology, 2020)
Why ocular mucosa is paucibacterial is unknown. Many different mechanisms have been suggested but the comprehensive experimental studies are sparse. We found that a deficiency in L-plastin (LCP1), an actin bundling protein, resulted in an ocular commensal overgrowth, characterized with increased presence of conjunctival Streptococcal spp. The commensal overgrowth correlated with susceptibility to P. aeruginosa-induced keratitis. L-plastin knock-out (KO) mice displayed elevated bacterial burden in the P. aeruginosa-infected corneas, altered inflammatory responses, and compromised bactericidal activity. Mice with ablation of LPL under the LysM Cre (LysM. CreposLPLfl/fl) and S100A8 Cre (S100A8.CreposLPLfl/fl) promoters had a similar phenotype to the LPL KOs mice. In contrast, infected CD11c.CreposLPLfl/fl mice did not display elevated susceptibility to infection, implicating the myeloid L-plastin-sufficient cells (e.g., macrophages and neutrophils) in maintaining ocular homeostasis. Mechanistically, the elevated commensal burden and the susceptibility to infection were linked to defects in neutrophil frequencies at steady state and during infection and compromised bactericidal activities upon priming. Macrophage exposure to commensal organisms primed neutrophil responses to P. aeruginosa, augmenting PMN bactericidal capacity in an L-plastin dependent manner. Cumulatively, our data highlight the importance of neutrophils in controlling ocular paucibacteriality, reveal molecular and cellular events involved in the process, and suggest a link between commensal exposure and resistance to infection.